Natural disasters and economic growth: A semiparametric smooth coefficient model approach - Nikos Fatouros; Yiguo Sun (Journal of Risk and Financial Management, 2020)
Despite the fact that growth theories suggest that natural disasters should have an impact on economic growth, parametric empirical studies have provided little to no evidence supporting that prediction. On the other hand, pure nonparametric regression analysis would be an extremely difficult task due to the curse of dimensionality. We therefore re-investigate the impact of natural disasters on economic growth, applying a semiparametric smooth coefficient panel data model that takes into account fixed effects. Our study finds evidence that the coefficient curve of investment is a U-shaped function of the severity of the natural disasters. Thus, for relatively small disasters, marginal returns to investment decrease on the severity of natural disasters. However, after a certain threshold, the coefficient of investment starts increasing as natural disasters become more severe.
Keywords: O31; O44; Q47; Q54; 330; economic growth; fixed effects; natural disasters; smooth coefficient; panel data models